Strength design of tubular textile composites for pipeline rehabilitation under internal pressure. (February 2022) - Fu, Lisong; Zhang, Shujie; Cao, Guoquan; Zhang, Ziwei; Wang, Rui
Abstract: The tubular textile composite material is lined on the inner wall of the pipeline by the inversion method, and realizes the structural or semi-structural repair of the pipeline in the form of "pipe in pipe". Under the action of inversion pressure and working internal pressure, its strength directly affects the repair effect. In this paper, the pressure in the process of inversion and conveying medium is discussed, using theories such as the thin-walled cylinder theory and Hooke's law to analyse the stress of composite materials under internal pressure of the pipeline, and strength calculation equations used in the structural or semi-structural repair are established. The strength design was carried out by taking drainage pipes as an example. The results show that in the structural repair pipeline, and there is a certain value in the range of pipe diameter 1200–1400 mm. When the pipe diameter is before a certain value, the strength of tubular textile composites is designed according to the stress generated by working internal pressure. After a certain value, the strength is designed according to inversion pressure. Moreover, in the semi-structural repair pipeline, the stress under working pressure is far less than that under inversion pressure, so the strength of the material is designed according to inversion pressure. Highlights: The pressure of tubular textile composites in the process of inversion and conveying medium is discussed. Using theories to analyse the stress of composite materials under internal pressure of the pipeline. Strength calculation equations used in the structural or semi-structural repair are established.